2000
DOI: 10.1128/iai.68.10.5764-5770.2000
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Biopolymers Enhance Antibody Responses to Mucosally Delivered Vaccine Antigens

Abstract: We have evaluated the ability of two carbohydrate biopolymers, chitosan and gellan, to enhance antibody responses to subunit influenza virus vaccines delivered to the respiratory tracts of mice. Groups of mice were vaccinated three times intranasally (i.n.) with 10 g of purified influenza B/Panama virus surface antigens

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 57 publications
4
55
1
2
Order By: Relevance
“…Chitosan has shown promising results in i.n. split virus vaccines in mice (Bacon et al 2000), split virus and protein vaccines in humans (Read et al 2005;Sui, Chen, Fang, et al 2010;Sui, Chen, Wu, et al 2010) and split virus and DNA vaccines in poultry (Tischer et al 2002;Worrall et al 2009;Huang et al 2010;Rauw et al 2010). However, in our study vaccination with chitosan-adjuvanted inactivated AIV and TMC inactivated AIV particles did not induce AIV-specific serum Ig (de Geus et al 2011).…”
Section: 2contrasting
confidence: 51%
“…Chitosan has shown promising results in i.n. split virus vaccines in mice (Bacon et al 2000), split virus and protein vaccines in humans (Read et al 2005;Sui, Chen, Fang, et al 2010;Sui, Chen, Wu, et al 2010) and split virus and DNA vaccines in poultry (Tischer et al 2002;Worrall et al 2009;Huang et al 2010;Rauw et al 2010). However, in our study vaccination with chitosan-adjuvanted inactivated AIV and TMC inactivated AIV particles did not induce AIV-specific serum Ig (de Geus et al 2011).…”
Section: 2contrasting
confidence: 51%
“…Chitosan has shown promising results in i.n. split virus vaccines in mice (Bacon et al, 2000), split virus and protein vaccines in human (Read et al, 2005;Sui et al, 2010a,b) and a split virus vaccine in poultry (Worrall et al, 2009;Rauw et al, 2010). It was previously shown that CT is an effective mucosal adjuvant in chicken (Vervelde et al, 1998), but CT cannot be used in the field because of its toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Hayvan hücrelerinde yapılan çalışmalarda da kitosanın hayvanların bağışıklık sistemlerini uyararak veya virüsün bağlanma reseptörleri ile hayvan hücresinin viral reseptörleri arasında gerçekleşen etkileşimi önleyerek antiviral etki sergilediği ifade edilmektedir [56,57]. …”
Section: Antiviral Mekanizmaunclassified